Strategi Digital Marketing Melalui Tiktok pada Ezan Garage - Ariyanto, Aris; Alfaris, Ali; Pratama, Andhito Okta; Habibi, Muhammad Alfatih; Raizan, Muhamad (Journal of Entrepreneurship & Technopreneurship, 2026)
The development of digital marketing has encouraged business actors to utilize social media as a strategic tool to enhance sales performance. This study aims to analyze the planning of a digital marketing strategy through the TikTok platform in increasing used motorcycle sales at Ezan Garage. A qualitative research method was employed in this study. In addition, SWOT analysis was used to identify the strengths, weaknesses, opportunities, and threats in the implementation of the digital marketing strategy. The results indicate that the utilization of TikTok through informative video content, unit reviews, consumer education, and interactive features such as live streaming and TikTok Shop is able to increase brand awareness, engagement, and consumers’ purchase intention. A well-planned and measurable digital marketing strategy has been proven to contribute positively to the increase in used motorcycle sales at Ezan Garage. This study is expected to serve as a reference for automotive MSMEs in designing effective social media–based digital marketing strategies